Learning Vue - Shavin, Maya (O'Reilly Media, Inc., 2023)
Learn the core concepts of Vue.js, the modern JavaScript framework for building frontend applications and interfaces from scratch. With concise, practical, and clear examples, this book takes web developers step-by-step through the tools and libraries in the Vue.js ecosystem and shows them how to create complete applications for real-world web projects. You'll learn how to handle data communication between components with Pinia architecture, develop a manageable routing system for a frontend project to control the application flow, and produce basic animation effects to create a better user experience. This book also shows you how to: Create reusable and lightweight component systems using Vue.js Bring reactivity to your existing static application Set up a project using Vite.js, a build tool for frontend project code management Build an interactive state management system for a frontend application with Pinia Connect external data from the server to your Vue application Control the application flow with static and dynamic routing using Vue Router Fully test your application using Vitest and Playwright.
Includes bibliographical references and index
Keywords: JavaScript (Computer program language); Web applications -- Programming